ANALISIS EFISIENSI DAN EFEKTIVITAS MANAJEMEN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA PERUSAHAAN KELOMPOK INDUSTRI OTOMOTIF DI BURSA EFEK INDONESIA - D. Pipy, Carolla Chyntia; Hidayat, M. Taufiq (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTWorking capital is very important for the company. Companies that do not have adequate working capital would be difficult to carry out its activities. Without sufficient working capital, a company will lose the opportunity to improve the quantity and quality of the product. Working capital has a very vital role for the survival of a company in achieving the aim of gaining profit. This study aims to determine the effect of working capital turnover, turnover of cash, accounts receivable turnover and inventory turnover on profitability, simultaneously or partially. The sample in this study is the automotive industry companies in the Indonesia Stock Exchange. The data used are the financial statements of the period 2010 to 2014. The data analysis technique used is multiple linear regression, F test and t test. The results showed that the turnover of working capital, cash turnover, receivable turnover and inventory turnover simultaneously affect the profitability. Working capital turnover did not affect the profitability. Cash turnover did not affect the profitability. Accounts receivable turnover affect the profitability. Inventory turnover affect the profitability. Keywords: working capital turnover, cash, accounts receivable, inventory, profitability